HEPARIN BINDING PROTEIN IN SEMEN OF BUFFALO BULL MIGHT BE RESPONSIBLE FOR BETTER SEMEN FREEZABILITY AND SUBSEQUENT FERTILITY - SINGH, AK; BRAR, PS; CHEEMA, RS (The Indian Journal of Animal Reproduction, 2022)
The present study determined the concentration of purified heparin binding proteins (HBP) in frozen-thawed spermatozoa of buffalo bulls and established the relationship of HBP with semen characteristics and fertility. About 50 frozen semen straws of same ejaculate per buffalo bull (n=30 bulls) were used to establish purified HBP concentrations in frozen-thawed spermatozoa extracts. On the basis of HBP, all the bulls were grouped as high fertility (HFB, >0.3 mg/109 sperms; n=15) or low fertility (LFB,
Keywords: Acrosome reaction; Buffalo bull; FSCR; Heparin binding proteins; Frozen semen